Cutaneous Manifestations in Juvenile Idiopathic Arthritis Patients, A Challenge in Diagnosis: A Case Report - Elza Wahyuni; Deryne Anggia Paramita; Kristo Alberto Nababan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Juvenile idiopathic arthritis (JIA) is a heterogeneous group of chronic arthritides in children under 16 years old, characterized by persistent arthritis of unknown etiology with variable systemic and extra-articular manifestations. Systemic juvenile idiopathic arthritis (sJIA) represents a distinct subtype with clinical features including intermittent high fever, arthritis, and cutaneous eruptions, which often pose diagnostic challenges due to overlapping manifestations with other autoimmune or vasculitic diseases. The purpose of reporting this case is to highlight the diagnostic challenges of sJIA with atypical cutaneous manifestations, which may mimic other autoimmune disorders, and to emphasize the importance of careful clinical evaluation for early recognition and management. We report the case of an 8-year-old girl who presented with generalized blackish maculopapular rash, butterfly-shaped erythematous plaques on the face, high intermittent fever, and symmetrical arthritis of both knees. Laboratory examinations revealed elevated inflammatory markers and liver enzymes, with negative antinuclear antibody and anti double stranded DNA results. The data were collected through patient follow-up during hospitalization and regular outpatient visits at the Dermatology, Venereology, and Aesthetics Polyclinic of H. Adam Malik Hospital Medan over a 3-month period. Histopathological findings showed vasculitis. Differential diagnoses considered were systemic lupus erythematosus (SLE) and Henoch-Schönlein purpura (HSP), which were excluded based on clinical, laboratory, and histopathological evaluations. The final diagnosis was systemic juvenile idiopathic arthritis. The patient was treated with methotrexate, folic acid, topical corticosteroids, and emollients, with gradual clinical improvement observed during follow-up. This case highlights the importance of recognizing cutaneous manifestations in JIA, which may mimic other systemic diseases, and emphasizes the role of a multidisciplinary approach for early diagnosis and management to prevent long-term complications.